The Impact of Financial Literacy and Lifestyle on the Use of Paylater (Case Study of Shopee paylater users at STIE Eka Prasetya) - Vioresca Prissillya; Susan Grace V Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to analyze the effect of financial literacy and lifestyle on the use of paylater. This study uses quantitative data with primary and secondary data sources. The population in this study were STIE Eka Prasetya students from 2021-2023 as many as 875 students. The sample of this study amounted to 100 respondents obtained from the Hair et al formula using purposive sampling data collection techniques. Data analysis and testing consists of validity test, reliability test, descriptive statistical test, classical assumption test, multiple regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and coefficient of determination test. The results showed that financial literacy has a partially significant effect on paylater with a t value of 13.515> ttable 1.98447. Lifestyle has a partially significant effect on paylater with a t value of 3.776> ttable 1.98447. Financial literacy and lifestyle simultaneously have a significant effect on paylater with an Fvalue of 91.457> Ftable value of 3.09 and a regression coefficient value of 65.3%.